Analisis Manajemen Pengelolaan Barang Milik Daerah Pada Pemerintah Daerah Kabupatenaceh Tenggara( Studi Kasus Pada Dpkkd Kabupaten Aceh Tenggara) - sabitah sabitah (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine the Management of Regional Property Management (BMD). The subject of this research is the Regional Financial and Wealth Management Office of Southeast Aceh Regency, while the object of research is fixed and non-permanent assets. This study uses a qualitative descriptive method, with the method of observation and literature. Regarding the Management of Regional Property Management in Southeast Aceh Regency. Based on preliminary research, Southeast Aceh Regency has been guided by the Regulation of the Minister of Home Affairs (Pemdagri) Number 13 of 2006 concerning Guidelines for Regional Financial Management. In the management of Regional Property, the constraint is the professionalism of human resources